Refractive Errors in School Going Children - Data from A School Screening Survey Programme - Harpal Singh; V K Saini; Akhilesh Yadav; Bharti Soni (Medsci Publications, 2013)
Background: The prevalence of blindness in children ranges from approximately 0.3/1000 children in affluent regions to 1.5/1000 in the poorest communities. the importance of early detection and treatment of ocular diseases and visual impairment in young is obvious. Aim and objective - The basic aim of this study was to assess the status of refractive errors in school going children through school screening program. Method: the study was done on students aged 05 years to 15 years, selected randomly from rural and urban schools in and around the periphery of Bhopal, Madhya Pradesh. Result: A total of 18,500 children were screened, Out of them 10730 were boys (58.00%) and rest 7770 (42.00%) were girls. Ocular morbidity (refractory errors) was found in 2422(13.09%) children out of which 1059 (5.72%) were boys and 1363(7.36%) were girls. Of these there were a total of 1,313 myopes ; 740 hypermetropes ; 277 with astigmatism and 92 amblyopic children. Conclusion: school screening program is an effective way to detect the causes of visual impairment in school children.